DYNAMIQUE DES POPULATIONS DE BIOMPHALARIA PFEIFFERI ET DE BULINUS GLOBOSUS EN ZONE D’ENDEMIE SCHISTOSOMIENNE EN COTE D’IVOIRE - Yapi Yapi Grégoire; Toure Mahama; Boka Ohoukou Marcel; Tia Emmanuel; Boby Ouassa Anne-Marie; Kadjo Kouamé Alphonse (European Scientific Journal, ESJ, 2014)
This study was conducted in the gastropod mollusks Biomphalaria pfeifferi and Bulinus globosus in schistosomiasis endemic area in the region of Man, western Côte d'Ivoire. It was performed in two forest sites where schistosomiasis is endemic with a prevalence of over 60 %.The general objectiveof this study isto know theseasonal variations ofintermediate hostsinorder to administerchemotherapyto patientsinthe absence orlow density ofmolluscsin water.Monitoring malacological population lasted three years and concerned two waterside villages (Botongouiné and Gueupleu) of‘’Ko’’, a tributary of the river ‘’N'Zo’’. Population dynamics of molluscswas studied in relation to some environmental factors. Molluscs sampling was achieved by two prospectors during 15 minutes per study site. The data indicate that the high apparent densities of Biomphalaria pfeifferi and Bulinus globosus were observed in the late dry season and early rainy season. In addition, we note that the variation of relative abundance of snail intermediate hosts is significantly influenced by rainfall and watercourseregime.